Phantoms in the mortuary-DNA transfer during autopsies - Schwark, T.; Poetsch, M.; Preusse-Prange, A.; Kamphausen, T.; Von Wurmb-Schwark, N. (Forensic Science International, 2012)
DNA evidence frequently plays an important role in criminal investigations and in some cases may be the only means of convicting a suspect. The constant improvement of DNA analysis techniques affords the individualization of minute amounts of DNA, aggravating the risk of contamination artifacts.In our study, we investigated the prevalence of DNA contamination in the autopsy facilities of the Institutes of Legal Medicine in Essen and Kiel (Germany). Using DNA-free swabs, we took samples from instruments used during autopsy and autopsy tables. Surfaces and instruments were routinely cleaned before sampling. Swabs were subjected to different PCRs to quantify the total amount of DNA and to amplify individual specific STR-markers. In most samples, alleles that could be linked to bodies that had been autopsied before were found. Furthermore, we could show that a DNA transfer from the autopsy table to a body was detectable in four out of six cases investigated. The interpretation of DNA typing results may thus be severely complicated. To avoid DNA contamination, we tried out different cleaning methods, of which only a bleach containing cleaner showed sufficient results. © 2011 Elsevier Ireland Ltd.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Autopsy; DNA contamination; Forensic; STR typing